Empirical analysis based on the related factors of college students’ mental health problems - Zhenhua, Huang; Nan, Wang (Frontiers in Psychology, 2022)
Interpersonal relationship is one of the important factors affecting college students' mental health. The relationship between interpersonal relationship and college students' mental health has also become a large number of academic research topics. In order to explore whether there is a correlation between optimism and college students' mental health, and if so, what kind of situation it presents. Based on literature review, mathematical statistics and questionnaire survey, this study optimized the iterative process of clustering algorithm. Extract valuable parts from a large amount of precipitation of students' psychological data, establish data models, and provide decision-making guidance for managers. The results show that there are significant differences between optimists and pessimists in optimistic factors and pessimistic factors. Optimists score significantly higher on optimistic factors than pessimists, while pessimists score significantly lower than pessimists. Conclusion optimism can significantly alleviate life stress and intervene psychological crisis.